Factors influencing the stated preference of university employees towards telecommuting in International Islamic University Malaysia - Ismail, Farah Diyanah; Kadar Hamsa, Abdul Azeez; Mohamed, Mohd Zin (Elsevier, 2016)
The problem of traffic congestion, especially in metropolitan areas clearly indicates that congestion is steadily worsening. Surprisingly, this trend is also predominant in the major higher learning institutions in Malaysia. The increasing private vehicle use by International Islamic University Malaysia (IIUM) community (both staff and students) has contributed to increase in traffic volume and thus developing long queues and traffic disturbances along the major road particularly during peak hours. In this context, telecommuting is seen as one of the supporting options to reduce the level of congestion and parking demand oncampus. The purpose of this paper is to examine factors that influence the stated preference of employees towards telecommuting adoption in IIUM. A questionnaire survey was administered targeting both academic and administrative staff of the University. The questionnaire consists of four sections, which are demographic profile, travel behaviours, work characteristics and perceptions on various aspects of telecommuting. The findings showed that concept of telecommuting were widely accepted by the IIUM employees. Presence of children, travel distance, travel time, delay time and frequency of face-to-face communication were significant factors contributing the academic employees to telecommute. However, only presence of children and frequency of face-to-face communication were significant factors influencing the choice of administrative staff towards telecommuting.